Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/2162402x.2015.1127495
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid-sensing toll-like receptors 3, 7 and 8 in esophageal epithelium, barrett’s esophagus, dysplasia and adenocarcinoma

Abstract: Toll-like receptors (TLRs) are immunological receptors recognizing various microbial and endogenous ligands, such as DNA, RNA, and other microbial and host components thus activating immunological responses. The expression of TLRs in esophageal adenocarcinoma is not well known. The aim of this study was to evaluate expression patterns of those TLRs that sense nucleic acids in Barrett's esophagus with and without dysplasia and in esophageal adenocarcinoma. TLRs 3, 7 and 8 were stained immunohistochemically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
(33 reference statements)
2
26
0
Order By: Relevance
“…Though, regulation of this translocation is reported to be controlled by UNC93B1 protein, its inhibition has only a partial effect on TLR3 mediated signaling (Bugge et al, 2017). Further, cell surface expression of TLR3 has been reported in a variety of cells such as pulmonary cells, hepatocytes, breast cancer, prostate cancer and epithelial adenocarcinoma (Salaun et al, 2006; Gambara et al, 2014; Helminen et al, 2016) indicate that it signaling occurs through the plasma membrane. Dynasore, a dynamin inhibitor that inhibits endocytosis of the receptors, only partially affects the poly(I:C) mediated TLR3 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, regulation of this translocation is reported to be controlled by UNC93B1 protein, its inhibition has only a partial effect on TLR3 mediated signaling (Bugge et al, 2017). Further, cell surface expression of TLR3 has been reported in a variety of cells such as pulmonary cells, hepatocytes, breast cancer, prostate cancer and epithelial adenocarcinoma (Salaun et al, 2006; Gambara et al, 2014; Helminen et al, 2016) indicate that it signaling occurs through the plasma membrane. Dynasore, a dynamin inhibitor that inhibits endocytosis of the receptors, only partially affects the poly(I:C) mediated TLR3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 induces a potent antigen-specific CD8+ T-cell responses that directly induces effector CD8+ T-cell and natural killer (NK) cells for IFN-γ release (Conforti et al, 2010). TLR3 was reported to be expressed not only by immune cells but also in the various cancer cells, such as breast cancers (Salaun et al, 2006), prostate cancer (Gambara et al, 2014), epithelial adenocarcinoma (Helminen et al, 2016), and others. Classically TLR3 signaling is mediated through the endosomal compartment of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although a possible association might be obscured by the limited number of observations in subgroup analysis, analogous results were presented by Helminen et al, who evaluated TLR-7 expression in esophageal adenocarcinoma, using immunohistochemistry. 20 Much research points at a dual or controversial role of TLR-7 in cancer development. [20][21][22][23] Whereas Lin et al showed down-regulation of TLR-7 gene expression in hepatocellular adenocarcinoma and hepatitis, Vaz and Andersson demonstrated its overexpression in pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…20 Much research points at a dual or controversial role of TLR-7 in cancer development. [20][21][22][23] Whereas Lin et al showed down-regulation of TLR-7 gene expression in hepatocellular adenocarcinoma and hepatitis, Vaz and Andersson demonstrated its overexpression in pancreatic ductal adenocarcinoma. 21,23 In summary, the role of TLR-7 expression and activation in adenocarcinomas remains unclear and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Toll like receptors 1, 2 and 6 recognise the cell wall lipid in bacteria and fungus (Chau et al, 2009;Talreja et al, 2003). Whereas, Toll like receptors 3, 7, 8 and 9 have been reported to recognise of viral nucleic acids (Alexopoulou et al, 2001;Helminen et al, 2016;Pohar et al, 2018). Other Toll like receptors such as TLR 4 and 5 recognise the envelope proteins and polysaccharides in bacterial and fungal cell walls (such as lipopolysaccharide, mannan and flagellin) (Akira & Takeda, 2004;Poltorak et al, 2000).…”
Section: Toll Like Receptors (Tlrs)mentioning
confidence: 99%